(untitled) (Mongolian Journal of Agricultural Sciences, 2022)
Deciduous trees of Ulmus species were reported to exhibit antibiotic, antifungal, antioxidant, anti-inflammatory, hepatoprotective, neuroprotective, antiangiogenic, and antiviral effects that rich in flavonoids. In this study, phytochemical analysis and pharmacological activities of Ulmus pumila L were studied. The upper parts of Ulmus pumila L plants were grinded and extracted in 80% ethanol with a ratio of 1:10, infusing by maceration method. The total crude extract was fractioned into a group of solvents with increasing polarity: hexane, chloroform, ethyl acetate, and n-butanol. The results of the toxicity test showed the safety of the oral ingestion and treatment with ethanolic and ethyl-acetic fractions decreased inflammatory symptoms and exhibited protective effects for carrageenan-induced paw edema. These preliminary findings may support its traditional medicinal use and could be promising candidate with application in the treatment of inflammatory symptoms.